2019
DOI: 10.1002/smtd.201900349
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Topological Insulators on Semiconductors (Bi2Se3/Te@Se) toward High‐Performance Photodetectors

Abstract: Heterojunctions, composed of different materials, are widely explored in optoelectronic devices thanks to their unique advantages, such as high carrier mobility and excellent photoelectronic characteristics. In this work, Bi2Se3/Te@Se heterojunctions (Bi2Se3/Te@Se) are synthesized through the epitaxial growth of Bi2Se3 nanosheets (Bi2Se3 NTs) on tellurium@selenium nanotubes (Te@Se NTs) by using a low‐cost and facile solvothermal process. Bi2Se3/Te@Se are further applied in high‐performance photoelectrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 82 publications
0
36
0
Order By: Relevance
“…11 b–d. Following this study, Zhang et al [ 139 , 140 ] demonstrated photodetectors based on Te@Bi and Te/Bi 2 Se 3 @Se heterojunctions. For the Te@Bi heterojunction, the corresponding photocurrent density and photoresponsivity in 0.5 M KOH solution as a function of incident laser power with a wavelength of 365 nm are presented in Fig.…”
Section: Applicationsmentioning
confidence: 75%
“…11 b–d. Following this study, Zhang et al [ 139 , 140 ] demonstrated photodetectors based on Te@Bi and Te/Bi 2 Se 3 @Se heterojunctions. For the Te@Bi heterojunction, the corresponding photocurrent density and photoresponsivity in 0.5 M KOH solution as a function of incident laser power with a wavelength of 365 nm are presented in Fig.…”
Section: Applicationsmentioning
confidence: 75%
“…The P ph further increases to 21.96 µA cm −2 under the irradiation of level IV, which is higher than those of the current state‐of‐the‐art PEC‐type PDs based on heterojunction nanomaterials such as Te@Bi, Te@Se, Bi 2 Se 3 /Te@Se NTs, and Bi/Te NSs (Table 2). [ 41–44 ] Interestingly, the calculated P ph and R ph of 3.5 g L −1 2D PbS NPLs‐based PDs are about 2.8 times of those based on 1 g L −1 2D PbS NPLs under the irradiation of 400 nm, while the ratios are 2.5, 3.2, 2.5, and 3.2 under the irradiation of 350, 475, 550, 650 nm lasers, respectively. The observed ≈200% photo‐response enhancements are in good agreement with the loading ratio (3.5:1), indicating that the 2D PbS NPLs are uniformly dispersed on the ITO glass (Scheme insert in Figure 6b).…”
Section: Resultsmentioning
confidence: 95%
“…For instance, 0.15/0.16 s is detected at 400 nm while it increases to 0.41/0.48 s at 650 nm laser in 0.001 m KOH. In addition, a fast t res / t rec time of 0.12/0.13 s has been achieved in 0.1 m KOH at 650 nm, which is a significantly lower value than or other nanomaterials such as InSe, [ 41 ] Bi 2 Se 3 /Te@Se, [ 52 ] and BP. [ 53 ] The low t res / t rec time can be ascribed to the fast generation and recombination of photo‐generated holes and electrons, which can be enhanced by tuning the light wavelength or improving the KOH concentration.…”
Section: Resultsmentioning
confidence: 99%